DEVELOPMENT OF EDUCATIONAL GAME BASED ON SOCIO-SCIENTIFIC ISSUES TO IMPROVE LOGICAL THINKING ABILITY - Ristanti, Arsyiska Nanda; Irawan, Edi (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Science learning requires a complex thinking process that must be developed in it. Logical thinking skills are needed in science learning because it helps students understand scientific concepts systematically and rationally. One of the learning media that can be used to improve logical thinking skills is Articulate Storyline which is integrated with Socio-Scientific Issues. This research uses the Research and Development (R&D) method with the ADDIE model. The data collection was carried out by expert validation, student questionnaires, and tests. The research subjects were students of class VII G State Islamic Junior High School 2 Ponorogo (MTsN 2 Ponorogo). The data obtained were analyzed for validity using the Aiken Index. Meanwhile, the questionnaire was analyzed using the average percentage and the test data was analyzed using the T-test and N-Gain. Based on the results of the research that has been obtained, the Aiken Index value is 0.95 with very valid validity. The practicality obtained a percentage of 83% with an increase in pretest and post test results for each indicator. Thus, this study shows that this media is effective in improving students' logical thinking. For further research, it is recommended to develop similar media applied to other topics and levels.